Svidersrky V.P., Konstantinova T.E., Danilenko I.A., Oleksandrenko V.P., Kirichenko L.M., Furman A.YU. Increase of wear resistance of locking elements of circular valve of comhressor of the motor-car filler gas station - Свідерський, В. П.; Константінова, Т. Є.; Даніленко, І. А.; Олександренко, В. П.; Кириченко, Л. М. (Problems of Tribology, 2018)
The analysis of terms of work of self-acting circular valve is executed. Research of wear resistance and mechanical properties of composition fluoroplastic materials of modified was shown a carbon fibre, coke and nanopowder of dioxide of zirconium expediency of their application for making of locking elements of valves.